Harmonisation of criminal policy on corruption offences in the criminal justice system in Indonesia - Nazhif Ali Murtadho; Muhammad Galuh Pamungkas Wahyu Ramadhan (Komisi Pemberantasan Korupsi, 2025)
Corruption in Indonesia remains entrenched due to fragmented criminal policies that separate formal criminal sanctions from informal social controls, thereby weakening comprehensive anti-corruption efforts. This paper examines the need to harmonise Criminal Policy, rooted in UNCAC ratification and legislative reform, with Non-Penal Policy, which relies on public awareness, informal sanctions, and cultural norms. Using doctrinal legal research with statutory and comparative approaches, the study analyses national legislation, UNCAC provisions, and best practices in criminalising bribery in the private sector. The findings indicate that although UNCAC ratification through Law No. 7/2006 modernised formal sanctions and introduced non-mandatory offences, gaps persist in the regulation of corporate bribery and a lack of systematic non-criminal measures, producing policy dissonance. The study demonstrates that integrating ISO 37001 standards, non-penal asset forfeiture, public integrity education, and community engagement can bridge these gaps. The researcher concludes that an integrated criminal policy incorporating clear criminal definitions, preventive education, and robust social sanctions is essential for sustainable corruption control. Accordingly, the paper recommends legislative amendments to fully criminalise private-sector bribery, institutionalise non-penal strategies, and establish coordinated oversight mechanisms to promote a cohesive, adaptive, and equitable anti-corruption framework.